Determinan Price Earning Ratio dan Stock Return (Studi pada Saham-Saham Syariah di Bursa Efek Indonesia) - Yanti, Mimi (Universitas Brawijaya, Indonesia, 2012)
This research aims at investigating and showing empirical evidence of the influence of the company's fundamental variables, comprising financial leverage, dividend payout ratio, standard deviation of earnings growth, and return on equity on the price earnings ratio, and the influence of the company's fundamentals factors and price earnings ratio on the stock return. Theoretically, the results of this research are expected to enrich and strengthen the issue in the field of investment, particularly the theory of stockvaluation, so it would be beneficial for scholars as well as the authorities of Islamic capital market and investors of sharia shares. The population of this study were sharia stocks at Indonesia Stock Exchange, that continuously recorded profit over five year period and paid the dividends. Using these criteria, a total of 22 companies were selected. The method of analysis was the Path analysis. The results indicated that the price earnings ratio of sharia stocks in Indonesia is determined by the dividend payout ratio, standarddeviation of earning growth and return on equity. The research also found that the price earning ratio and return on equity determine the stock returns. Thus, fundamental variables are important sources of information to determine the price earnings ratio and stock returns and could be used by investors in deciding their investment strategies.